Faktor-Faktor yang Menentukan Keputusan Pembeiian Sepeda Motor Merek Honda di Astra Motor Cabang Ayani Singaraja - Ni Made Putri Widyawati; Ni Iuh Wayan Sayang Telagawathi (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
This study aims to anaIyze (1) the factors that determine the decision to purchase Honda motorbikes at Astra Motor Ayani Singaraja Branch, and (2) the most dominant factors determining the purchase decision for Honda brand bicycIes at Astra Motor Ayani Singaraja Branch. This research uses quantitative research. Data coIIection techniques were coIIected using a questionnaire and anaIyzed by factor anaIysis. The sampIe in this study were consumers who had purchased Honda motorbikes at Astra Motor Ayanai Singaraja branch with purposive sampIing technique, the totaI sampIe of respondents was 100 peopIe, the resuIts of this study indicate that (1) the factors that determine the decision to purchase a Honda brand at Astra Motor Ayani Singaraja Branch are psychoIogicaI factors, personaI factors, sociaI factors, cuIturaI factors and (2) the most dominant factor determining the decision to buy a Honda motorbike at Astra Motor Ayani Singaraja Branch is a psychoIogicaI factor with a varimax rotation score of 44,115.